A novel frameshift mutation in TRPV6 is associated with hereditary pancreatitis - Shah, Idrees A.; Prasad, Hari; Banerjee, Sanghita; Kurien, Reuben Thomas; Chowdhury, Sudipta Dhar; Visweswariah, Sandhya S. (Frontiers in Genetics, 2023)
Hereditary pancreatitis (HP) is a rare debilitating disease with incompletely understood etio-pathophysiology. The reduced penetrance of genes such as PRSS1 associated with HP indicates a role for novel inherited factors. We performed whole-exome sequencing of three affected members of an Indian family (Father, Son, and Daughter) with chronic pancreatitis and compared variants with those seen in the unaffected mother. We identified a novel frameshift mutation in exon 11 of TRPV6 (c.1474_1475delGT; p.V492Tfs*136), a calcium channel, in the patients. Functional characterization of this mutant TRPV6 following heterologous expression revealed that it was defective in calcium uptake. Induction of pancreatitis in mice induced TRPV6 expression, indicating that higher expression levels of the mutant protein and consequent dysregulation of calcium levels in patients with chronic pancreatitis could aggravate the disease. This novel mutation in a family with HP emphasizes the need to expand the list of genes used currently for the evaluation of patients with hereditary pancreatitis.